“Do not look at me like that”: Is the facial expression score reliable and accurate to evaluate pain in large domestic animals? A systematic review - Fischer-Tenhagen, Carola; Meier, Jennifer; Pohl, Alina (Frontiers in Veterinary Science, 2022)
Introduction Facial expression scoring has proven to be useful for pain evaluation in humans. In the last decade, equivalent scales have been developed for various animal species, including large domestic animals. The research question of this systematic review was as follows: is facial expression scoring (intervention) a valid method to evaluate pain (the outcome) in large domestic animals (population)? Method We searched two databases for relevant articles using the search string: “grimace scale” OR “facial expression” AND animal OR “farm animal” NOT “mouse” NOT “rat” NOT “laboratory animal.” The risk of bias was estimated by adapting the Quality Assessment of Diagnostic Accuracy Studies (QUADAS) checklist. Results The search strategy extracted 30 articles, with the major share on equids and a considerable number on cows, pigs, and sheep. Most studies evaluated facial action units (FAUs), including the eye region, the orbital region, the cheek or the chewing muscles, the lips, the mouth, and the position of the ears. Interobserver reliability was tested in 21 studies. Overall FAU reliability was substantial, but there were differences for individual FAUs. The position of the ear had almost perfect interobserver reliability (interclass coefficient (ICC): 0.73–0.97). Validity was tested in five studies with the reported accuracy values ranging from 68.2 to 80.0%. Discussion This systematic review revealed that facial expression scores provide an easy method for learning and reliable test results to identify whether an animal is in pain or distress. Many studies lack a reference standard and a true control group. Further research is warranted to evaluate the test accuracy of facial expression scoring as a live pen side test.